Avaliação tomográfica do côndilo mandibular e via aérea superior durante o uso de aparelho intraoral (BRD) em pacientes com apneia obstrutiva do sono - Castelo, Keila Maria de Sousa (2025)
Introduction: Intraoral Mandibular Advancement Devices (MAD) for the treatment of obstructive sleep apnea (OSA) promote position changes in mandibular condyles. However, no study has evaluated the variability of condylar displacement and how it affects the upper airway dimensions/polysomnographic parameters. Objective: To evaluate the displacement of the mandibular condyles, when using MAD, by tomographic images of the temporomandibular joints, as well as to evaluate if this displacement influences the dimensions of the upper airway and the polysomnographic parameters. Material and Method: The sample consisted of 17 volunteers (08 men and 9 women) aged between 27 and 62 years; BMI 27kg / m2; clinical and polysomnographic diagnosis of mild and moderate OSA (AHI> 5 / h and <30 / h, with at least one sign and / or symptom of OSA). The study was divided into 2 phases: baseline (without AIOAM) and final evaluation (AIOAM in 85% of the maximum mandibular advancement - therapeutic position). Measurements in the temporomandibular joint and airways were performed using images obtained from Conical Beam Computed Tomography before the installation of the MAD and after reaching 85% of the maximum mandibular advancement. In these two times, polysomnographic records were also performed. The MAD used was the BRD (Brazilian Dental Appliance). Results: With the MAD in therapeutic position, we found a significant reduction in AHI (P = 0.04), an increase in the minimum oxyhemoglobin saturation (P = 0.01), extrusion (P = 0.001) and anteriorization (P = 0.001) of the condyles. There was also an increase in velopharyngeal (P = 0.02) and retrolingual (P = 0.008) volumes and in the retrolingual area (P = 0.002). There was a correlation between the amount of condylar extrusion and the velopharyngeal area (P = 0.03), velopharyngeal volume (P = 0.001) and more constricted velopharyngeal area (P = 0.03). The anterior displacement of the condyle had a significant correlation with the retrolingual volume (P = 0.02). Conclusion: The amount of vertical and horizontal displacement of the condyles and the final condylar position reached seems to influence dimensional parameters of the airway.